FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR IPS TERPADU - Kharisma Idola Arga; Vetri Yanti Zainal (JURNAL ELASTISITAS: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2019)
This research analyzes the factors that affect the achievement of learning IPS Terpadu grade VIII SMP Wiyata Bhakti Natar that is learning interest and learning activity. Research methods used descriptive verifikatif design with Ex Post Facto and Survey approach. The population in the research at the grade eighth of SMP Wiyata Bhakti Natar 2017/2018 which amounted to 85 students, The sample was taken by using Slovin with Probability sampling, number of the sample was 70 students and using proportional random sampling. Collecting data through observation, interview, documentation and questionnaire. Result of the research shows that: (1) There is positif and sygnificant influence of learning interest to the result of learning IPS Terpadu at the grade eighth of SMP Wiyata Bhakti Natar 2017/2018. (2) There is positif and sygnificant influence of learning activity to the result of learning IPS Terpadu at the grade eighth of SMP Wiyata Bhakti Natar 2017/2018. (3) There is positif and sygnificant influence of learning interest and learning activity to the result of learning IPS Terpadu at the grade eighth of SMP Wiyata Bhakti Natar 2017/2018.